2020
DOI: 10.1002/alz.043975
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive decline is associated with longitudinal cerebral blood flow reductions and gray matter atrophy in older adults

Abstract: Background Subjective cognitive decline (SCD), a potential harbinger of Alzheimer’s disease (AD), has been cross‐sectionally associated with neurodegeneration and cerebrovascular disease markers on brain MRI. However, longitudinal associations are less clear with few existing studies that yield inconsistent findings. Here, we related baseline SCD to longitudinal structural and hemodynamic markers of brain health in older adults free of clinical dementia and stroke. Methods Vanderbilt Memory & Aging Project par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another community-based study also found higher CBF in the left parahippocampal gyrus of individuals with SCD compared to those without SCD (Wenyi Li et al, 2022), suggestive of neurovascular dysregulation (Hays et al, 2016; Østergaard et al, 2013; Wierenga et al, 2014). Moreover, a longitudinal study showed that baseline SCD (measured as a continuous variable in a community-based sample) was associated with reduced global CBF in older adults over a 3.8 year follow-up period (Kresge et al, 2020). Given the importance of CBF to maintaining brain health and supporting cognitive function, and its role as a potential early marker of cognitive decline (Hays et al, 2016; Rabin et al, 2017; Wierenga et al, 2014), research is needed to better understand if SCD is associated with CBF in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Another community-based study also found higher CBF in the left parahippocampal gyrus of individuals with SCD compared to those without SCD (Wenyi Li et al, 2022), suggestive of neurovascular dysregulation (Hays et al, 2016; Østergaard et al, 2013; Wierenga et al, 2014). Moreover, a longitudinal study showed that baseline SCD (measured as a continuous variable in a community-based sample) was associated with reduced global CBF in older adults over a 3.8 year follow-up period (Kresge et al, 2020). Given the importance of CBF to maintaining brain health and supporting cognitive function, and its role as a potential early marker of cognitive decline (Hays et al, 2016; Rabin et al, 2017; Wierenga et al, 2014), research is needed to better understand if SCD is associated with CBF in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…One efficient and inexpensive method of screening and identifying patients at increased risk of AD is through utilizing measures of subjective cognitive decline (SCD). Higher levels of SCD have been associated with cognitive decline, 4,5 hippocampal atrophy, 6 changes in cerebral blood flow, 6 and progression to MCI and dementia. 7 Despite the utility of SCD in predicting AD-related brain and clinical changes, there are numerous factors beyond AD that can contribute to SCD and many clinical and demographic factors that may modify the ability of SCD to predict AD-related changes.…”
Section: Introductionmentioning
confidence: 99%